2014
DOI: 10.1186/1471-2474-15-418
|View full text |Cite
|
Sign up to set email alerts
|

Pain medication management of musculoskeletal conditions at first presentation in primary care: analysis of routinely collected medical record data

Abstract: BackgroundPrimary care pharmacological management of new musculoskeletal conditions is not consistent, despite guidelines which recommend prescribing basic analgesics before higher potency medications such as opioids or non-steroidal inflammatory drugs (NSAIDs).The objective was to describe pharmacological management of new musculoskeletal conditions and determine patient characteristics associated with type of medication prescribed.MethodsThe study was set within a UK general practice database, the Consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…The possible association between low nSES and increased odds of opioid prescription is in agreement with Ndlovu et al's study finding that higher neighborhood deprivation was associated with higher risk of opioid prescription. 26 Ndlovu 26 also found that the majority of patients received no pharmacologic therapy, much the same as this study. However, this study presents contrast with the findings of Joynt et al 15 , which noted low nSES was associated with a 24% decrease in odds of opioid prescription.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The possible association between low nSES and increased odds of opioid prescription is in agreement with Ndlovu et al's study finding that higher neighborhood deprivation was associated with higher risk of opioid prescription. 26 Ndlovu 26 also found that the majority of patients received no pharmacologic therapy, much the same as this study. However, this study presents contrast with the findings of Joynt et al 15 , which noted low nSES was associated with a 24% decrease in odds of opioid prescription.…”
Section: Discussionsupporting
confidence: 72%
“…In particular, lower nSES was associated with a lower likelihood of patient's receiving an opioid prescription, independent of race. In contrast, Ndlovu et al 26 found the opposite effect; that higher levels of neighborhood deprivation was associated with higher likelihood of strong analgesic (mostly opioid) therapy. Thus, patients living in postal codes with more poverty were more likely to receive an opioid.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A study in Canada reported that almost 10% of patients were prescribed NSAIDs despite patients' high risk for renal and cardiovascular complications (28). Another study in the UK on patients with moderate to severe CKD reported 5.7% NSAID use (29). Given that some NSAIDs are also available over the counter, their use is likely to be higher than the estimates reported here using general practice prescription data.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, pharmacologic options, such as acetaminophen and nonsteroidal anti-inflammatory drugs (NSAIDs), are used to manage musculoskeletal pain, and muscle relaxants may be used to manage muscle pain, stiffness, and spasm 1417. Although there are many skeletal muscle relaxants, systemically active products are generally available with prescription and are associated with well-documented adverse effects such as somnolence, dizziness, weakness, and dry mouth 17…”
Section: Introductionmentioning
confidence: 99%